Differences in soil nutrient and microbial characteristics between invasive Ageratina adenophora and native plant communities - Tian Wu; Qinghong Duan; Hongbin Zhang; Weiming Xiu; Zhilin Jiang (PLoS ONE, 2025)
Much emphasis has been placed on the negative consequences of alien species on resident ecosystems. Nevertheless, quantitative studies on the effects of invasive and native plant communities on soil nutrients and microbial features were rarely conducted. This study investigated soil microbes and soil nutrients associated with different degrees of Ageratina adenophora invasion and plant communities (Gramineae and Dicotyledons). The correlations between soil microbes and soil nutrients were analyzed. The findings indicated that the invasion of A. adenophora markedly elevated the levels of soil total nitrogen (TN), nitrate nitrogen (NO3--N), ammonium nitrogen (NH4+-N), available potassium (AK) and available phosphorus (AP), while decreasing the concentrations of soil total phosphorus (TP) and total potassium (TK) in comparison with those in non-invaded areas. The concentrations of NO3--N, NH4+-N, and AK in strongly invasive plant communities were significantly greater than those in the Gramineae and Dicotyledon groups. The soil microbial richness of the A. adenophora invasive plant community was higher than that of the native plant community. In contrast, the soil microbial evenness was lower than that of the native plant community, but the soil microbial dominance increased with the increasing degree of A. adenophora invasion. Meanwhile, the number of soil bacteria, fungi, actinomycetes, nitrogen-fixing bacteria, potassium-solubilizing bacteria and phosphate-solubilizing bacteria in the invasive plant community increased significantly with increasing degree of A. adenophora invasion. The soil microbial richness of the invasive plant community dominated by A. adenophora was higher than that of the native plant community. In contrast, soil microbial evenness was reduced in the invasive community compared to the native plant community, while microbial dominance increased with the extent of A. adenophora invasion. The number of bacteria, fungi, actinomycetes, nitrogen-fixing bacteria, potassium-solubilizing bacteria and phosphate-solubilizing bacteria in the soil of the invasive plant community increased significantly. Furthermore, the variation trend of the Simpson diversity index (D) was that of the Shannon diversity index (H) of the soil microbes in this study. The McIntosh diversity index (U) showed a consistent decrease with the increasing degree of A. adenophora invasion. Moreover, after the correlation coefficients between soil microbes and nutrients were analyzed, we found that there was a significant positive correlation between soil nutrients and microbial richness in both the A. adenophora invasive community and the native plant community. Compared with plant communities, A. adenophora invasion can greatly alter the soil nutrient and microbial characteristics and the trade-offs of soil nutrients supply and demand, which may facilitate growth. The soil microbial diversity in different communities may be important factors that led to changes of soil nutrients. A. adenophora altered the trade-offs of soil nutrients supply and demand by changing the composition and diversity of soil microbes, which may be a critical ecological mechanism of the successful invasion of the exotic weed A. adenophora successful invasion.